ANALYZING COLLABORATIVE GOVERNANCE IN COMMUNITY-BASED TOURISM DEVELOPMENT: EVIDENCE FROM HARAPAN VILLAGE, BARRU REGENCY USING NVIVO - Rosdiana; A.Aminah (P3M Stia Al Gazali Barru and Meraja media, 2026)
[Full Paper] to pdf Copyright (c) 2026 Meraja journal